The sustainable development consequences of IMF debt vs. capital control: comparing progress in GPI and GDP terms for Korea and Malaysia - Mohamad, Azhar; Hashim, Mastura; Sifat, Imtiaz Mohamma (Elsevier Ltd, 2019)
The panic wrought by the 1997 Asian financial crisis spurred different mitigative measures. Some states assented to IMF bailout and restructuring, while others enforced capital control. Since then, despite intense academic and regulatory scrutiny of the nuances of the recession, empiric focus on recovery trajectory of affected countries centred chiefly around traditional GDP metrics; an approach that disregards economic performance in a manner congruent with Sustainable Development Goals (SDG). In this paper, we adopt a broader SDG-compatible approach by tracking two affected countries’ (Korea and Malaysia) recovery via operationalizing an alternative growth indicator GPI (Genuine Progress Indicator). First, we construct a 35-year long GPI index from 1980 to 2014 and employ the Solow Growth Model to measure the impact of the two remedial measures on GDP and GPI of both countries. Employing an ARDL approach, we find external debt to impact significantly the GDP and GPI of Korea. Meanwhile for Malaysia, the controversial capital control failed to register significant impact. Moreover, unemployment rates, trade openness, fixed capital formation and the history of previous crises are found to be influential determinants of GDP and GPI, with credit and exchange rate variables showing ambiguous results.